Analisis Faktor Penentu Agresivitas Pajak Perusahaan Indeks LQ45 - Ramadhani, Syifa Alvernia Jasmin; Sandra, Amelia; Bunfa, Liaw (E-Jurnal Akuntansi, 2024)
This research was conducted to obtain evidence regarding the influence of inventory intensity, capital intensity, intangible assets intensity, and profitability on LQ45 index companies listed on the Indonesia Stock Exchange in 2020-2022. The number of samples taken was 14 companies with 42 observations that met the sample selection criteria determined using the purposive sampling method. The research analysis technique is multiple linear regression analysis. The research results stated that the research data passed the pooling test, classical assumption test, multiple linear regression test, and hypothesis test. Based on the results of the analysis, it was found that inventory intensity had no negative effect on indications of tax aggressiveness and intangible assets intensity had no positive effect on indications of tax aggressiveness. Meanwhile, capital intensity and profitability have a positive effect on the indication of tax aggressiveness, meaning that the higher the capital intensity and profitability, the higher the level of indication of tax aggressiveness. Keywords: Inventory Intensity; Capital Intensity; Intangible Assets Intensity; Profitability; Indication of Tax Aggressiveness